2006
DOI: 10.17796/jcpd.30.4.540025283p827511
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of newer sedatives in conscious sedation

Abstract: This double blind study was undertaken to determine the safety and efficacy of orally administered newer sedatives and analgesics for conscious sedation in 120 child patients. Patients were randomly assigned into: Midazolam (I), Ketamine (II), Zolpidem (III), Midazolam plus Ketamine (IV), Midazolam plus Tramadol (V) and Zolpidem plus Tramadol (VI) groups of 20 each. Onset of action, level of sedation, ease of treatment completion, recovery time, and post-operative amnesia were assessed for all and compared. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Benzodiazepines, used solely or in combination, were the most well-studied drugs: only 7 out 54 trials did not include a benzodiazepine group [13,17,30,38,46,49,65]. Drugs currently used in clinical practice are reported in the following studies: midazolam was investigated in 33 trials [7, 1416, 19, 27, 28, 31, 33, 35, 39–45, 47, 48, 5054, 59, 61, 63, 66–71], nitrous oxide in seven [26, 30, 34, 42, 46, 50, 51], ketamine in eight [13–17, 26, 34, 37, 44, 49, 70], dexmedetomidine in one [49] and propofol in four [13, 14, 46, 47]. Besides, all drugs investigated in 23 studies were the ones currently used: 19 involved midazolam [7, 19, 27, 31, 33, 35, 40, 41, 5052, 54, 61, 63, 66–70], three nitrous oxide [46, …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Benzodiazepines, used solely or in combination, were the most well-studied drugs: only 7 out 54 trials did not include a benzodiazepine group [13,17,30,38,46,49,65]. Drugs currently used in clinical practice are reported in the following studies: midazolam was investigated in 33 trials [7, 1416, 19, 27, 28, 31, 33, 35, 39–45, 47, 48, 5054, 59, 61, 63, 66–71], nitrous oxide in seven [26, 30, 34, 42, 46, 50, 51], ketamine in eight [13–17, 26, 34, 37, 44, 49, 70], dexmedetomidine in one [49] and propofol in four [13, 14, 46, 47]. Besides, all drugs investigated in 23 studies were the ones currently used: 19 involved midazolam [7, 19, 27, 31, 33, 35, 40, 41, 5052, 54, 61, 63, 66–70], three nitrous oxide [46, …”
Section: Resultsmentioning
confidence: 99%
“…Benzodiazepines were compared to non-benzodiazepines in 13 studies [18,44,45,48,50,51,5660,70,71]. In four studies, anterograde amnesia was significantly more likely when benzodiazepines were used than when nitrous oxide [50], antihistamines [45,48,60], or triclofos [48] were used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no RCTs found looking at side effects alone. After combining the results from Medline and Embase searches and removing papers that did not meet the criteria, 16 papers were included [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . Data from these papers are summarised in Table 1.…”
Section: Randomised Controlled Clinical Trials Of Effectiveness and Rmentioning
confidence: 99%
“…One study comparing agents for conscious sedation in children concluded that midazolam and ketamine were most effective in combination 10. Other studies in children have questioned the benefit of adding midazolam, demonstrating equally effective sedation properties and no difference in the incidence of emergence phenomena with intravenous ketamine alone compared with the combination of agents 11.…”
Section: Discussionmentioning
confidence: 99%